Analysis of guessing meaning in the context strategy for reading comprehension skill in the English language learning in the students of 3rd of Bachillerato, class “B” at “La Salle” High school of Velasco parish, in the city of Riobamba, Chimborazo province, during the academic year 2015-2016 - Ordóñez León, Andrés Ismael (2017)
This research focuses on strategies for guessing meanings of words since the main problem presented by the students of the 3rd Baccalaureate Class "B" at Unidad Educativa "La Salle" in the city of Riobamba, during the academic period 2015-2016, which are 31 men and 12 women, lies in the construction of new vocabulary to understand written texts. The objectives of this research work are to observe the strategies to guessing meaning through the context, which help the students to obtain a general idea of the reading, as well as to analyze the role of the context, and the strategies applied by the teacher in the teaching-learning process. The type of study applied is qualitative because it studies the quality of the activities applied by the teacher, also it is exploratory because it only explores the guiding questions and the research topic with different levels of depth. The qualitative method used was the ethnographic method. The technique used is the observation with a passive role. The instrument used for the collection was a tally sheet, describing the possible strategies which the students better understand the texts or which activities the teacher performed. In this way the data could be analyzed by the researchers. As a conclusion of the results, it was obtained that the teacher hardly ever applies strategies of guessing meaning to help students to get a better understanding of readings passages, since the teacher is not familiarized with strategies to infer the possible meanings of unknown words.